3-point function of currents for holographic cosmology and monopole non-Gaussianities - Cravo, Matheus [UNESP]; Nastase, Horatiu [UNESP] (Springer Nature, 2024)
In this paper we present the calculation of the three-point function in momentum space of currents for a SO(3) global symmetry, in a three-dimensional toy model within phenomenological holographic cosmology. Since the two-point function gives, via electric-magnetic duality, the resolution of the cosmological monopole problem, the three-point function is related to the monopole non-Gaussianities. We check that the final result is UV and IR finite and satisfies the transverse Ward identities and consider the k1 ≪ k2, k3 case, relevant for cosmology. We also show that the two-loop result for the 3-point function is completely independent of the explicit form of the potential, meaning that, like the solution to the monopole problem, also the non-Gaussianities are universal within the phenomenological holographic cosmology.